EFEKTIFITAS DIAPHRAGMATIC BREATHING TERHADAP DERAJAT DISPNEA PADA PENDERITA TB PARU MDR DI RUMAH SAKIT AMINAH KOTA TANGERANG - Gustina, Putri; Silaen, Harsudianto (Universitas Murni Teguh, 2023)
Pulmonary Tuberculosis (TB) Disease which damages the respiratory tract, and causes in respiratory problems that usually lead to ventilation dysfunction. The aim of this study is to analyze the effectiveness of diaphragmatic breathing on the degree of dyspnea in patients with Pulmonary TB in the Jasmine Room at Aminah Hospital, Tangerang City. The research design is Quasi-experimental in one group with pre and post-test using total sampling technique. The number of respondents were 33 patients with Pulmonary TB who were hospitalized. participated in this study using this technique. Sampling Total Sampling. Researchers instrument for the diaphragmatic breathing program that can be done is by practicing regularly for 2 weeks, where in 1 week you can do 3 times diaphragmatic breathing exercises. Meanwhile, to measure the degree of dyspnea using the Modified Medical Research Council (mMRC) scale, then a Checklist. Statistical test uses a Wilcoxon test. Based on the research results obtained with a p value of 0.000 <0.05, which means that there is an effect of the effectiveness of diaphragmatic breathing on the degree of dyspnea in MDR pulmonary TB patients at Tangerang City Hospital in 2021, the degree of dyspnea in MDR pulmonary TB patients after using diaphragmatic breathing is 17.00. This shows that the Degree of Dyspnea after the Use of Respiratory Muscles 33 patients experienced a decrease in the Degree of Dyspnea by 17 times from the Degree of Dyspnea prior to the Use of Diaphragmatic Breathing. Abstrak Penyakit Tuberkulosis Paru (TB) yang merusak saluran pernapasan, dan mengakibatkan gangguan pernafasan yang biasanya dapat menyebabkan disfungsi ventilasi. Penelitian ini bertujuan untuk menganalisis Efektifitas Diaphragmatic Breathing Terhadap Derajat Dispnea Pada Penderita TB Paru Di Ruang Melati Rumah Sakit Aminah Kota Tangerang Tahun. Desain penelitian Kuasi Eksperimen pada one group with pre and post-test dengan menggunakan teknik pengambilan sampel Total Sampling. Jumlah responden adalah 33 orang pasien Penderita TB Paru yang di rawat inap. Instrumen penelitian untuk Program pelaksanakan Diaphragmatic breathing yang dapat dilakukan yakni dengan latihan secara rutin selama 2 minggu, dimana dalam 1 minggu dapat dilakukan latihan selama 3 kali latihan diaphragmatic breathing. Sedangkan untuk mengukur derajat Dispnea menggunakan Modified Medical Research Council (mMRC) scale, kemudian lembar ceklis. Uji statistik Uji Wilcoxon. Berdasarkan hasil penelitian didapatkan p value 0,000 < 0,05 yang berarti sehingga ada Pengaruh Efektifitas Diaphragmatic Breathing Terhadap Derajat Dispnea Pada Penderita Tb Paru MDR di Rumah Sakit Kota Tangerang Tahun 2021, Derajat Dispnea Pada Pasien Tb Paru MDR sesudah Penggunaan Diaphragmatic Breathing adalah 17,00. Hal ini menunjukan bahwa Derajat Dispenea setelah Penggunaan Otot Pernafasan 33 pasien mengalami penurunan Derajat Dispnea sebesar 17 kali dari Derajat Dispenea sebelum dilakukan Penggunaan Diaphragmatic Breathing.